Pathological Tumor Regression Grade Classifications in Gastrointestinal Cancers: Role on Patients' Prognosis. (December 2019) - Fanelli, Giuseppe N.; Loupakis, Fotios; Smyth, Elizabeth; Scarpa, Marco; Lonardi, Sara; Pucciarelli, Salvatore; Munari, Giada; Rugge, Massimo; Valeri, Nicola; Fassan, Matteo
Preoperative chemotherapy or combined radiotherapy and chemotherapy (CRT), followed by surgery, represents the standard approach for locally advanced esophageal, gastric, and rectal carcinomas. To adequately evaluate the effects of neoadjuvant CRT in the resection specimens, several histopathologic tumor regression grade (TRG) scoring systems have been introduced into clinical practice. The primary goal of these TRG systems relies on a correct prognostic stratification of patients in the attempt to help clinical decision-making and influence surgical strategies, postoperative adjuvant therapies, and surveillance intensity. However, most TRG systems suffer from poor reproducibility and low interobserver concordance rates. Many efforts have been made in the identification of alternative, robust, simple, and universally accepted TRG scoring systems, which would help in the comparison of different treatment strategies and in the standardization of multimodal therapies. The aim of this review is to analyze the most commonly used TRG systems in gastrointestinal cancers highlighting their pitfalls and usefulness, depending on the tumor type.